2021
DOI: 10.1590/fst.38619
|View full text |Cite
|
Sign up to set email alerts
|

Response surface optimization of polysaccharide extraction from Galla Chinensis and determination of its antioxidant activity in vitro

Abstract: Galla Chinensis was a traditional Chinese medicine used as an ingredient in many prescriptions for the treatment of oxidant damage-associated symptoms in China. The current research on the isolation of polysaccharides from Galla Chinensis and their antioxidant activities still remain as an ongoing challenge. The purpose of this study is to develop an isolation technique for polysaccharides from Galla Chinensis and determine their antioxidant properties in vitro. An ultrasonic-assisted method of polysaccharides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Similarly, Hu et al reported a maximum activity of 0.25 at 350 µg/mL for polysaccharides extracted by ultrasound from Galla chinensis at 60 °C, 20 min, and 40 mL/g [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Hu et al reported a maximum activity of 0.25 at 350 µg/mL for polysaccharides extracted by ultrasound from Galla chinensis at 60 °C, 20 min, and 40 mL/g [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al reported that the polysaccharides extracted using ultrasound exhibit lower metal chelation power than those by maceration. The maximum chelation activity is 38% for ultrasound and 86% for maceration at 5 mg/mL [ 40 ]. Similar findings were reported by Surin et al The authors obtained an IC 50 of 1.25 and 3.7 mg/mL for polysaccharides extracted by maceration and by ultrasound, respectively [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that MSC conditioned media protects myocardial cells from oxidative stress and reduces the severity of inflammatory arthritis and immune response (Dong, 2015;Kay et al, 2017). It may also cause neuroinflammation, exacerbate oxygen and glucose deficiencies, thereby leading to cell death (Horn et al, 2011;Khan et al, 2021;Hu et al, 2021). Ruiz et al revealed that MSC conditioned medium can lead to proliferation or death of hepatocellular carcinoma cells, depending on the source of stem cells, and Maj et al found that MSC conditioned medium may inhibit the damage caused by chemotherapy and become a potential alternative drug for urinary tract tumors (Ruiz et al, 2013;Maj et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Dry fruiting bodies powder (400 g) was boiled in water for 3 times (6 h for each) (Hu et al, 2021;. The supernatant was concentrated after centrifugation.…”
Section: Extraction and Purification Of Polysaccharidesmentioning
confidence: 99%